Meta-Analisis: Efektivitas Penggunaan Mhealth terhadap Kepatuhan Mengkonsumsi Suplemen Zat Besi dan Asam Folat pada Wanita Hamil - Nuryuliana Nuryuliana (Jurnal Ventilator, 2025)
Compliance with iron and folic acid supplementation is an important factor contributing to the prevention and treatment of anemia in pregnant women to meet the nutritional needs of the fetus during pregnancy. The use of mobile health interventions (mHealth) such as SMS reminders, voice messages, videos and telephones can provide behavioral support and health education needs of pregnant women. determine the effectiveness of mHealth use on compliance with iron and folic acid supplementation (IFAS) among pregnant women. Systematic review and meta-analysis wre conducted using PRISMA guidelines and PICO models which included Population = pregnant women; Intervention = mHealth, Comparison = does not use mHealth; Outcome = compliance with iron and folic acid supplementation. Articles were collected through databases such as BMJ, Google Scholar, PubMed, Open Journal System. 6 articles met the inclusion criteria for meta-analysis and were assessed using RevMan 5.3. Meta-analysis from Kenya, India, Brazil and Indonesia showed that pregnant women who used mHealth services were 1.87 times more likely to adhere to iron and folic acid supplements compared to those who did not use mHealth and the effect was statistically significant (OR= 1.87; 95% CI= 1.10 to 3.16; p <0.001). The use of mHealth can improve compliance of pregnant women in consuming iron and folic acid supplements.